Potency of Mangrove Apple (Sonneratia alba) as Mercury Bioindicator - Muhammad Reza Cordova; Fajar Dwi Maulana Eftiah; Neviaty Putri Zamani (Journal Omni-Akuatika, 2017)
The anthropogenic provide a negative impact on the surrounding environment. Mangrove species, such as Sonneratia alba would get the impact of anthropogenic activities, to accumulate the pollution of heavy metals. The aim of this study were to evaluate mercury accumulation in Mangrove Apple (S. alba) and to analyze mangrove apple potency as mercury bioindicator. Samples were taken in April 2016 at Pari Island, Seribu Islands by purposive sampling. The results showed that the highest concentration of Hg in the Northern of Pari Island was found in the leaves and the lowest was in the fruit. The highest concentration of Hg in the Eastern of Pari Island was found in the leaves and lowest was in the fruit. The concentrations of Hg in the Eastern area higher the Northern area (significantly different). The accumulation of Hg mainly collected on the leaves with TF> 1, but the ability of S. alba trees absorb Hg in the environment showed a small value, namely BCF <1. The ability of S. alba in sediments, contaminated with mercury showed a high value of the leaves in the East Pari Island, but the fruit of S. alba both in the North and East of the Pari Island showed a small value.  Mangrove Apple leaves has a potency as mercury bioindicator organ.